P561 Impact of ustekinumab TDM on clinical practice: a multi-centre, prospective, cross-sectional observational trial—mUST-Decide. (25th January 2019) - Bressler, B; Dajnowiec, D; Williamson, M; Karra, K; Long-Long, G; Sattin, B; Afif, W
Abstract: Background: Therapeutic drug monitoring (TDM) is an important part of the management of biologics used in the treatment of IBD. Current understanding of ustekinumab (UST) TDM is limited and its value in clinical practice is unknown. We hypothesised that addition of UST TDM to clinical practice would alter clinical decisions in the treatment of Crohn's disease (CD). Methods: We enrolled 112 consecutive UST-treated CD patients across 11 sites in Canada from April 2017 to January 2018. HBI, CRP, baseline characteristics and clinical decisions were recorded for 110 subjects at the single study visit, faecal calprotectin (FCP) was performed (local lab, standard of care) and blood was drawn for TDM (Sanquin, UST RIA). TDM results were provided at the end of the study, and sites recorded a hypothetical clinical decision with UST TDM ± FCP. Congruency of the actual (D1) and hypothetical decisions (D2 (clinical + TDM), D3 (clinical +TDM and FCP)) were assessed using McNemars paired χ 2 test. A four- member expert panel examined all cases (3 experts/case) and made decisions by majority consensus – all D1 first, then all D2, then all D3. Experts were provided with additional training on UST PK data and interpretation, but decisions were not protocolised. Results: Patients enrolled in the study were highly refractory (90% aTNF exposed, median 16.2 years of CD) but 70% were in clinical remission (HBI <5). At a population level, no differences could be detected before and after the introduction of TDM alone ( p = 1.0), or TDM + FCP ( p = 0.86). However, at a patient level, 39% of D2 decisions changed and 50% of D3 changed (see table). Examining the expert panel decisions at a population level, no differences could be detected before and after the introduction of TDM alone ( p = 0.16), while decisions with TDM + FCP were significantly different ( p = 0.0006). At the patient level with TDM alone, 23% of individual decisions changed and 67% of decisions were different when incorporating TDM + FCP. No new safety signal was observed, no patient samples were positive for ADAb to UST. Conclusions: At a population level, introduction of UST TDM into routine clinical practice did not significantly impact clinical decisions for clinicians or experts, but adding FCP significantly altered clinical decisions for experts, but not clinicians. The divergence in impact of TDM and FCP between clinicians vs. experts highlights a need for greater education. Further study to clarify the use and impact of these tests in a proactive setting is warranted.